SOSIALISASI MENINGKATKAN KESEIMBANGAN DINAMIS LANSIA DENGAN TERAPI LATIHAN TRADISIONAL TAICHI PADA LANSIA DI PEMATANGSIANTAR - Muliati, Muliati; Marolop Parlindungan Napitu; Isa Harpika Br. Ginting; I Ngurah Gede Verar Fujastawan; Margaretha Togatorop (Yayasan Nusantara Hasana Berdikari, 2025)
Decreased dynamic balance in the elderly is a major factor that increases the risk of falls and reduces quality of life. Preventive efforts through safe and structured physical exercise are needed, one of which is traditional Tai Chi exercise therapy. This community service activity aimed to improve the knowledge and skills of the elderly in maintaining dynamic balance through Tai Chi exercises in Pematangsiantar. The methods used included socialization, Tai Chi movement training, mentoring, and evaluation. The results showed an improvement in the elderly’s understanding of the importance of balance as well as their ability to independently perform Tai Chi movements. In addition, there was an improvement in body balance, increased confidence in movement, and a reduced risk of falls. Therefore, Tai Chi can be an effective and safe alternative exercise to improve dynamic balance in the elderly sustainably